Management Strategy of Paloh Naga Traditional Culinary Tourism in Denai Lama Village, Pantai Labu District - Sudirman, Sudirman; Sinaga, Amelia Sari Alam; Rosramadhana, Rosramadhana; Saepudin, Asep (Journal of Nonformal Education, 2022)
This study found the novelty of the fact that the enthusiasm of visitors was high enough to come just to enjoy a traditional culinary breakfast. The purpose of this study is to contribute to knowledge of the strategies used in the Paloh Naga traditional market. The type of research used is descriptive with a qualitative approach with the research subject of two (two) managers. Interviews, observation, and documentation are the data collection techniques used. The results show that the planning carried out in the traditional market is running quite well, as evidenced by the achievement of the goals that have been achieved, and the manager is also planning in as much detail as possible until the development plan is finalized. In organizing, there are still overlapping tasks in the division of tasks. The movement carried out by the manager is to hold regular meetings to motivate traders. Supervision has been carried out quite well, but there are still shortcomings that cause management to not be good enough.